2013
DOI: 10.1111/jth.12252
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin inhibition by the serpins

Abstract: To cite this article: Huntington JA. Thrombin inhibition by the serpins. J Thromb Haemost 2013; 11 (Suppl. 1): 254-64.Summary. Thrombin is the central protease in the blood coagulation network. It has multiple substrates and cofactors, and it appears that four serpins are responsible for inhibiting the thrombin produced in haemostasis and thrombosis. Structural studies conducted over the last 10 years have resolved how thrombin recognises these serpins with the aid of cofactors. Although antithrombin (AT), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
82
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(83 citation statements)
references
References 64 publications
1
82
0
Order By: Relevance
“…Heparin cofactor II (HCII), another serpin that is potentiated by heparin, is a coagulation inhibitor that inhibits only thrombin; HCII is reported to also inhibit Pharmacology of Heparin and Related Drugs chymotrypsin and neutrophil cathepsin G (Huntington, 2013). HCII is present in plasma at similar levels to AT (Tollefsen, 1997), but HCII cannot substitute for AT in AT deficiency.…”
Section: Other Heparin-activated Serpinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heparin cofactor II (HCII), another serpin that is potentiated by heparin, is a coagulation inhibitor that inhibits only thrombin; HCII is reported to also inhibit Pharmacology of Heparin and Related Drugs chymotrypsin and neutrophil cathepsin G (Huntington, 2013). HCII is present in plasma at similar levels to AT (Tollefsen, 1997), but HCII cannot substitute for AT in AT deficiency.…”
Section: Other Heparin-activated Serpinsmentioning
confidence: 99%
“…The combination of GAGinitiated reactive center loop expulsion with exposure of a protease-binding exosite is controlled by AT and HCII in contrasting ways, as shown in Fig. 5B (Huntington, 2013(Huntington, , 2014.…”
Section: Other Heparin-activated Serpinsmentioning
confidence: 99%
“…Thrombin and plasmin are serine proteases that are converted from their inactive zymogen forms (prothrombin and plasminogen) by the prothrombinase complex, and by tissue plasminogen activator (tPA), respectively (17,30,37). Suppression of thrombin and plasmin is accomplished by inhibiting the generation of the active enzymes, and/or by removing the active enzymes, from the circulation.…”
mentioning
confidence: 99%
“…3 A number of inhibitors of thrombin have been identified that limit the vascular consequences of inadvertent or pathophysiological thrombin generation, including antithrombin III, heparin cofactor II, protein C inhibitor, and nexin I, all of which belong to the serpin family of protease inhibitors. 4 In contrast, COMP is a member of the thrombospondin (TSP) protein family. COMP, also known as TSP5, is an abundant extracellular matrix protein expressed in tissues of the musculoskeletal system including cartilage and tendon.…”
mentioning
confidence: 99%